Pattern of cardiovascular diseases in Sudurpaschim province according to echocardiography findings - Adhikari, KC; Chaudhary, S; Joshi, NP; Shah, R; Bist, A (Devdaha Medical Journal, 2025)
Introduction: Cardiovascular diseases (CVDs) are the leading cause of globally, with rising incidence in low-and middle-income countries like Nepal. Understanding regional patterns is critical for targeted interventions. This study sheds light on the pattern of CVDs seen in patients coming to the only government hospital with cardiologists in Sudurpaschim Province.Methods: A cross-sectional observational study was conducted at Seti Provincial hospital from 1st January to 31st December 2023. All patients undergoing echocardiography during the study period were included. Data on demographics, history, and echocardiographic findings were collected using a standardized proforma and analyzed using SPSS. Diagnoses were made based on American Society of Echocardiography (ASE) guidelines for comprehensive transthoracic echocardiography and World Heart Federation (WHF) criteria for rheumatic heart disease (RHD).Results: A total of 3,971 patients were enrolled with 53.8% female. Most patients were over 12 years of age (97.7%). The majority were from Kailali district (50.8%) and the Terai region (70.5%). Habitual smoking was observed in 31.5% of patients. Echocardiography showed normal findings in 27.02%. Common abnormalities included valvular heart disease (12.28%), hypertensive heart disease (12.13%), pulmonary artery hypertension (14.90%), and rheumatic heart disease (6.5%). Cardiomyopathies were found in 8.89% (5.4% dilated, 3.3% ischemic). Congenital heart diseases (2.49%) were predominantly acyanotic.Conclusion: The burden of CVDs in Sudurpaschim Province is substantial. Valvular, hypertensive, and rheumatic heart diseases are common. Targeted screening and healthcare strengthening are essential for early detection and management.